The Effect of Insulin Feedback on Closed Loop Glucose Control - Steil, Garry M.; Palerm, Cesar C.; Kurtz, Natalie; Voskanyan, Gayane; Roy, Anirban; Paz, Sachiko; Kandeel, Fouad R. (The journal of clinical endocrinology and metabolism, 2011)
Context:Initial studies of closed-loop proportional integral derivative control in individuals with type 1 diabetes showed good overnight performance, but with breakfast meal being the hardest to control and requiring supplemental carbohydrate to prevent hypoglycemia.Objective:The aim of this study was to assess the ability of insulin feedback to improve the breakfast-meal profile.Design and Setting:We performed a single center study with closed-loop control over approximately 30 h at an inpatient clinical research facility.Patients:Eight adult subjects with previously diagnosed type 1 diabetes participated.Intervention:Subjects received closed-loop insulin delivery with supplemental carbohydrate as needed.Main Outcome Measures:Outcome measures were plasma insulin concentration, model-predicted plasma insulin concentration, 2-h postprandial and 3- to 4-h glucose rate-of-change following breakfast after 1 d of closed-loop control, and the need for supplemental carbohydrate in response to nadir hypoglycemia.Results:Plasma insulin levels during closed loop were well correlated with model predictions (R = 0.86). Fasting glucose after 1 d of closed loop was not different from nighttime target (118 ± 9 vs. 110 mg/dl; P = 0.38). Two-hour postbreakfast glucose was 132 ± 16 mg/dl with stable values 3–4 h after the meal (0.03792 ± 0.0884 mg/dl · min, not different from 0; P = 0.68) and at target (97 ± 6 mg/dl, not different from 90; P = 0.28). Three subjects required supplemental carbohydrates after breakfast on d 2 of closed loop.Conclusions/Interpretation:Insulin feedback can be implemented using a model estimate of concentration. Proportional integral derivative control with insulin feedback can achieve a desired breakfast response but still requires supplemental carbohydrate to be delivered in some instances. Studies assessing more optimal control configurations and safeguards need to be conducted.